Nepalese People’s Knowledge about Tuberculosis - Bhatt, CP; Bhatt, AB; Shrestha, B (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2010)
Introduction : Tuberculosis (TB) is a major cause of illness and death worldwide, especially in Asia and Africa. Objective: Objective of this study was to determine Nepalese people's knowledge about tuberculosis. Methods : The diagnosed cases of tuberculosis was randomly selected, structured questionnaires were used to collect patient knowledge about tuberculosis. Results : This prospective study included 300 diagnosed cases of pulmonary tuberculosis who were attending the DOTS programme of Nepal. Tuberculosis was most commonly found in economically active age group (21-50 years old). The incidence of tuberculosis was found higher in male than female. Regarding the common part of the body affected by TB bacilli 58% correctly said that it is the Lungs. About the mode of transmission of tuberculosis 50% knew that it is transmitted by droplet infections. More then two third of the respondents had knowledge about the clinical symptoms of tuberculosis, among them chronic cough (82%), evening rise of temperature (72%) and blood in the sputum (72%) were the major symptoms described. Only 16.6% of the respondents knew that Tuberculosis is an common opportunistic infection in people infected with HIV/AIDS. 53.3% patients responded correctly that body secretion like sputum contains Tubercle Bacilli and regarding disposal of sputum and other body fluids 30% said that incineration is the proper way of disposal. On prevention of spread of tuberculosis 31.6% said that TB patients should use mask. Conclusion : The study found that majority of the patients had satisfactory knowledge about the signs and symptoms of Tuberculosis but their knowledge about causative agent for Tuberculosis, disposal method for sputum and body fluid and preventive method for tuberculosis was still low. It is recommended that National tuberculosis control authority should design health education programme focusing on causative agents, disposal of sputum and body fluids and prevention of Tuberculosis. The awareness campaign should be targeted to patients, family members, community and health care providers and should be disseminated through the media that will reach the general Public. Such awareness campaign will increase the patient's general awareness about the disease and will help to reduce transmission of disease, prevent drug resistant cases and improve the efficacy of DOTS programme. Keywords : HIV/AIDS; TB; Mycobacterium tuberculosis DOI: 10.3126/saarctb.v6i2.3055 SAARC J. Tuber. Lung Dis. HIV/AIDS 2009 VI (2) 31-37